Analysis of Pollutant Sources from Community Health Center Activities in Mataram City - Nurhidayah, Nurhidayah; Sholehah, Hijriati; Nurhidayatullah, Nurhidayatullah; Mulhidin, Mulhidin; Abdullah, Taufik (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2024)
Health centers are health service facilities that produce waste containing microorganisms, toxic chemicals and radioactive materials that are dangerous and can pose risks to health and the environment. The purpose of this study was to determine the sources of health center waste and the types of waste from health center activities. This research method is a type of cross-sectional study, and data collection is done by filling out a questionnaire. The results of the study are the sources of health center waste, namely from the activities of the dental clinic, laboratory, Maternal and Child Health room, and the Emergency Unit room. The types of health center waste are liquid, domestic, solid medical, and toxic and hazardous. For the processing of liquid waste, all health centers in Mataram City have adequate wastewater treatment plants, either with a biofilter wastewater treatment plant system or other types of wastewater treatment plants, from 11 health centers, which have carried out sorting and have temporary storage places, namely 8 health centers. The process of managing medical waste involves sorting, transportation, storage and final processing with a third party. The weak point of B3 waste management is in the recording and sorting system of B3 solid waste and routine reporting of environmental management efforts and environmental monitoring efforts to related agencies that have not been able to be carried out by all existing health center agencies.